2017
DOI: 10.1177/1971400916689343
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis in subdural myeloid sarcoma

Abstract: Introduction A 74-year-old man presented to hospital with a headache, thrombocytopaenia and an acute deterioration in cognition on a background of acute monocytic leukaemia in remission. Method This is a case report with computed tomography (CT), magnetic resonance (MR) and histopathology imaging. Results Preoperative CT and limited MR demonstrated a subdural lesion with marked midline shift. Craniotomy performed for evacuation of the presumed subdural haematoma revealed a solid tumour-like lesion. Histopathol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…8 In the brain, MS frequently involves the parenchyma (43-54%), followed by dura (41%). 2,8 Though deemed rare, several large treatment trials and case series have been published in the literature reporting CNS-MS. [9][10][11][12][13][14][15][16][17] In the Children's Cancer Group (CCG) protocols for intensive-timing chemotherapy treatment for AML, 10 the authors reported that of the 1459 patients, 19 (1%) had CNS-MS, while the NOPHO (Nordic Society of Pediatric Hematology and Oncology)-AML 2004 trial of 315 patients found 22 (7%) had CNS disease but only 2 had MS in the dural/epidural space. 9 The pathogenesis of CNS infiltration is unclear; it is hypothesized that leukemic cell infiltrates are capable of migration from the bone marrow of the periosteum to the dura, into the underlying brain parenchyma once there is disruption of the pial-glial barrier.…”
Section: Topic Review: Dr Gharementioning
confidence: 99%
“…8 In the brain, MS frequently involves the parenchyma (43-54%), followed by dura (41%). 2,8 Though deemed rare, several large treatment trials and case series have been published in the literature reporting CNS-MS. [9][10][11][12][13][14][15][16][17] In the Children's Cancer Group (CCG) protocols for intensive-timing chemotherapy treatment for AML, 10 the authors reported that of the 1459 patients, 19 (1%) had CNS-MS, while the NOPHO (Nordic Society of Pediatric Hematology and Oncology)-AML 2004 trial of 315 patients found 22 (7%) had CNS disease but only 2 had MS in the dural/epidural space. 9 The pathogenesis of CNS infiltration is unclear; it is hypothesized that leukemic cell infiltrates are capable of migration from the bone marrow of the periosteum to the dura, into the underlying brain parenchyma once there is disruption of the pial-glial barrier.…”
Section: Topic Review: Dr Gharementioning
confidence: 99%